2018
DOI: 10.1002/14651858.cd009269.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial interventions to reduce alcohol consumption in concurrent problem alcohol and illicit drug users

Abstract: Analysis 1.1. Comparison 1 Cognitive-behavioural coping skills training (CBCST) versus twelve-step facilitation (TSF) programme, Outcome 1 Alcohol abstinence as number achieving 3 or more weeks of consecutive alcohol abstinence during treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 115 publications
1
28
0
1
Order By: Relevance
“…Furthermore, when screening does occur in these settings it is often completed without the use of a validated screening tool [7, 58]. Suggested reasons for these findings identify time restrictions, lack of resources and physician attitudes about the effectiveness of screening and brief intervention for the detection and management of alcohol misuse [52]. …”
Section: Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, when screening does occur in these settings it is often completed without the use of a validated screening tool [7, 58]. Suggested reasons for these findings identify time restrictions, lack of resources and physician attitudes about the effectiveness of screening and brief intervention for the detection and management of alcohol misuse [52]. …”
Section: Screeningmentioning
confidence: 99%
“…Furthermore a pilot study and randomized controlled trial have identified motivational interviewing to be an effective strategy to reduce alcohol consumption among alcohol misusing methadone maintained participants [51, 53]. Though not specific to OAT participants, psychosocial interventions for alcohol misuse among concurrent substance users have been described in a systematic review [52]. Four studies involving 594 participants evaluated 6 psychosocial interventions through 4 comparison groups: cognitive-behavioral coping skills training versus 12-step facilitation (n = 41) [63], brief intervention versus treatment as usual (n = 110) [64], hepatitis health promotion versus motivational interviewing (n = 256) [51] and brief motivational intervention versus assessment only group (n = 187) [65].…”
Section: Managementmentioning
confidence: 99%
“…However, intervention trials generally target a single substance rather than dual-substance problems, leaving a smaller literature on dual-focused interventions. Literature reviews of existing studies show promise for such dual-focus interventions (Arias & Kranzler, 2008; Klimas et al, 2014). However, none of these studies included HIV samples, and to our knowledge, no other published trials examined dual drug-and-alcohol-focused interventions in HIV-infected samples.…”
Section: Introductionmentioning
confidence: 99%
“…Hulshof and Hoenen 2007; Joosen et al 2015; Kinnunen-Amoroso 2013). The Cochrane work group has conducted a number of systematic reviews, summarizing the body of knowledge-related occupational health and safety (e.g., Klimas et al 2014; Ruotsalainen et al 2015). In Sweden, the government decided to initiate an investigation into how to secure and develop the competence of the OHS.…”
Section: Introductionmentioning
confidence: 99%